Development, Characterization and Stability Evaluation of Topical Gel Loaded With Ethosomes Containing Achillea millefolium L. Extract - Andleeb, Mehwish; Shoaib Khan, Haij Muhammad; Daniyal, Muhammad (Frontiers in Pharmacology, 2021)
Background The delivery of plant extract at high loading with intact antioxidants and efficient skin permeation always remains a challenging task. To solve this, we prepared a stable gel formulation containing nanoethosomes loaded with Achillea millefolium (AM) extract for topical drug delivery. Method The AM extract was tested for phytochemical analysis, antioxidant activity, total phenolic and flavonoid contents and FTIR examination. Nanoethosomes containing AM extract were synthesized and characterized by size, zeta analyzer, scanning electron microscopy (SEM) and entrapment efficiency (EE) was determined. The optimized nanoethosomes were then incorporated to develop topical gel formulation and subjected to skin for permeation, pH, viscosity and organoleptic evaluation for three months. Results The AM ethanolic extract demonstrated about 88% free radical scavenging activity and notable phenolic and flavonoid contents upto 123 mg GAE/gand 42mg QE/g, respectively. The optimized nanoethosomes filled with AM extract were spherical, 240 nm in size with surface charge of -31.1 mV and showed very high entrapment efficiency (90%). The selected topical gel remained stable during study period. Exvivo permeation study of ethosomal gel showed highest percentage of 79.8%.